FLOOD HAZARD ASSESSMENT USING GEOGRAPHIC INFORMATION SYSTEMS IN THREE CITIES IN ECUADOR AT A SCALE OF 1:5000 - Morales Donoso, Karla Gabriela (2025)
Floods in Ecuador are recurrent and caused by various reasons such as heavy rains associated with the El Niño phenomenon, river overflows or deforestation. This study focused on delimiting flood hazard zones in three cities in the coastal region of Ecuador: Esmeraldas, Chone and Guayaquil, using geoinformation at a scale of 1: 5,000, generated by the IGM. Using GIS tools and the expert or multicriteria method, the interaction between conditioning factors (slope, texture and water table) and the triggering factor (precipitation) was carried out. The results indicate that in Esmeraldas, Chone and Guayaquil there are areas with high hazard (409 ha, 5 079 ha, 3 449 ha, respectively). The hazard categorization (high, medium, low, none) varies according to the combination of slope, texture, water table and precipitation in each specific area. This approach provides detailed information for risk management and decision making in territorial planning.